Kondisi Overcrowded dengan Ketepatan Tindakan Initial Assesment - Ariska, Ariska (JURNAL ILMIAH KESEHATAN MANADO, 2025)
Overcrowded is an increase in the number of patient visits to the ER at one time. Initial assessment is a basic assessment carried out in the first minutes of crisis management for very serious trauma victims and this determines the victim's health. The aim of the research is to determine the relationship between overcrowded conditions and the accuracy of initial assessment actions at the Bayangkara Tk.III Manado Hospital Emergency Room. This research is quantitative, with a research design that is analytical descriptive using a cross sectional method. The research was carried out in May 2025 at the Bayangkara Tk.III Manado Hospital Emergency Room. The population in this study were all nurses at the Bayangkara Tk.III Manado Hospital Emergency Installation with a total of 31 people. The sample in this study was taken by total sampling, namely 31 respondents. The statistical test used was the Spearman's rho test with a significance level of 95% (α=0.05). The results obtained in overcrowded conditions were mostly busy, namely 14 respondents (45.2%), while the initial assessment actions were mostly correct, namely 19 respondents (61.3%). The results of the Spearman's rho statistical test obtained a value of P = 0.000 or P < 0.05. The conclusion from the research results is that there is a relationship between overcrowded conditions and the accuracy of initial assessment actions in the Bayangkara Tk.III Manado Hospital Emergency Room. Suggestions for hospitals can be used as reference material regarding the accuracy of initial assessment actions so that they can increase professional health workers in all areas of action by holding training for health workers in order to prevent overcrowding in the ER.